Diagnostic value of serum amyloid A in differentiating the inflammatory disorders in wild birds - Rhim, Haerin; Kim, Myeongsu; Gim, Seulgi; Han, Jae-Ik (Frontiers in Veterinary Science, 2024)
Introduction: Rescued wild birds have very high rates of inflammatory diseases; however, there are have been limitations in assessing them sensitively. Few studies have examined acute phase proteins in wild birds. In this study, serum amyloid A (SAA) was evaluated as an inflammatory indicator, along with traditional indices, such as; white blood cell count, albumin, orand albumin/globulin ratio. Methods: In total, 291 samples from 139 birds of six avian species were analyzed. All samples were divided into four groups (severe, moderate, mild injuries, and clinically healthy) based on clinical examinations and evaluated by group. SAA levels were measured using an anti-chicken SAA ELISA kit, and compared with leukocyte counts, albumin concentrations, and albumin/globulin ratios were compared. Differences among groups were evaluated using the Kruskal-Wallis test, followed by a post-hoc test using Dunn's multiple comparisons with SPSS V27. Statistical significance was set at p < 0.05. Results: The median concentration and standard deviationinterquartile range (ng/ml) of SAA in each